UMP signed MOU with Selahuddin Eyyubi University (SEU) - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) continued to attract world attention as marked by the latest signing of a Memorandum of Understanding (MoU) with Selahuddin Eyyubi University (SEU) from Turkey on February 4, 2016.